2017
DOI: 10.1038/s41467-017-00529-0
|View full text |Cite
|
Sign up to set email alerts
|

A prophage tail-like protein is deployed by Burkholderia bacteria to feed on fungi

Abstract: Some bacteria can feed on fungi, a phenomenon known as mycophagy. Here we show that a prophage tail-like protein (Bg_9562) is essential for mycophagy in Burkholderia gladioli strain NGJ1. The purified protein causes hyphal disintegration and inhibits growth of several fungal species. Disruption of the Bg_9562 gene abolishes mycophagy. Bg_9562 is a potential effector secreted by a type III secretion system (T3SS) and is translocated into fungal mycelia during confrontation. Heterologous expression of Bg_9562 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
101
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(105 citation statements)
references
References 51 publications
4
101
0
Order By: Relevance
“…The genus Burkholderia constitutes a large group of bacterial species, being present as soil dwellers or living in association with plants, animals, fungi (endosymbiont) and insects (as symbiont) 3739 . Recently, we had demonstrated that the rice associated Burkholderia gladioli strain NGJ1 utilizes a type III secretion system (T3SS) to feed on fungi (phenomenon known as mycophagy) 40 . In this study, we report that the NGJ1 bacterium not only has antifungal activity, but it also has anti-bacterial activity and that it utilizes two different type VI secretion systems (T6SS-1 and T6SS-2) to kill co-habiting bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The genus Burkholderia constitutes a large group of bacterial species, being present as soil dwellers or living in association with plants, animals, fungi (endosymbiont) and insects (as symbiont) 3739 . Recently, we had demonstrated that the rice associated Burkholderia gladioli strain NGJ1 utilizes a type III secretion system (T3SS) to feed on fungi (phenomenon known as mycophagy) 40 . In this study, we report that the NGJ1 bacterium not only has antifungal activity, but it also has anti-bacterial activity and that it utilizes two different type VI secretion systems (T6SS-1 and T6SS-2) to kill co-habiting bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Partial fragments (~300 bp) of one of the core T6SS apparatus genes of T6SS-1 ( VipA ) and T6SS-2 ( ImpE ) were PCR amplified from the genomic DNA of B. gladioli strain NGJ1 using gene specific primers (Supplementary Table 6) and cloned into pK18 mob vector. The recombinant plasmid was electroporated (Gene pulsar XcellTm; BioRad) into B. gladioli strain NGJ1, as per the method described in 40 . The insertion mutants were selected on kanamycin and rifampicin containing KBA (King’s medium B Base; Himedia, India) plates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A minimum of three leaves per plant and minimum 10 plants of each line per experiment was infected. However for tomato infection, the detached leaves (n=3) of at least 10 plants were used in each experiments (57). On the basis of observed symptom patterns (severe or mild or no symptoms), we categorised percentage of leaves having particular disease symptom as disease index.…”
Section: Methodsmentioning
confidence: 99%
“…The AtRAV1 gene was cloned in pET28a bacterial expression vector using RAV1OX-F and RAV1OX-R gene specific primers and transformed into E. coli (BL-21 strain, DE3-codon + ) cells. The protein was purified using affinity chromatography (Ni +2 -NTA) following the method described earlier (57). Similarly, the different variants of AtRAV1 , having different phosphorylation residues mutated (SDM1: Ser310Ala; SDM2: Thr19Ala; SDM3: Thr23Ala; SDM4: Thr193Ala; SDM5: having all four potential phosphorylation sites mutated) were synthesized commercially (Gene Universal Inc; http://www.geneuniversal.com/) and cloned in pET28a to purify different variant proteins.…”
Section: Methodsmentioning
confidence: 99%